Community involvement as a strategy for accountability corporate performance rating assessment program (Proper) - Najib, Akhmad; Emirzon, Joni; Zulkifli, Hilda; Alfitri, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Program Performance Rating (PROPER) is believed to encourage environmental requirements for business activities in environmental protection and management. The basic principle of the implementation of the PROPER is to encourage compliance of companies in environmental management through the instrument of information in the form of incentives and disincentives. Incentives in the form of image for companies that have good environmental management performance and disincentive given the reputation for poor environmental management system. In reality its implementation PROPER found weaknesses that lead to the assumption that the outcome of the PROPER not transparent, less credible and accountable in the public eye. This study aims to reveal what caused PROPER transparent, less credible and accountable in the eyes of society, then answer how the strategy should be done to improve the credibility PROPER. The approach taken in this study is a qualitative approach, with survey respondents are people around the range-1 PROPER participating companies in the city of Palembang. Data collection techniques include in-depth interviews, observation and documentation, while the technique of data analysis include: data reduction, data presentation, data interpretation, and conclusions. The results showed that 1) PROPER not transparent, less credible and accountable in the public eye due to no disclosure of information from the government and the company to the public regarding PROPER so that differences in perceptions create public dissatisfaction over the implementation and results of PROPER assessment. 2) Involvement of the public through publications in general and given the right to express an opinion on the objection period to answer what is the PROPER public discontent in the implementation and produce policies that are transparent, credible and accountable.